RESEARCHING PSYCHOLOGICAL ASPECTS OF MANAGEMENT: SUPPORTING SUBORDINATES AS A KEY FACTOR IN LEADERSHIP - POCHTOVIUK, Andrii; BILYK, Maryna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article analyses the key aspects of managerial activity, including management styles, methods of influencing staff and strategies of managerial behaviour. The article deepens scientific understanding of the psychological qualities of managers focused on subordinates, including their emotional intelligence, communication skills and social responsibility. Administrative, sociological, psychological and socio-psychological methods of management are considered, which allow to effectively regulate interaction in the team and create a favourable working climate. Particular attention is paid to the role of leadership, power and communication skills of the manager, in particular the importance of emotional intelligence in the management process. The importance of a balance between control and flexibility is emphasised, which contributes to employee productivity and motivation. The article highlights various forms of interaction between managers and their subordinates: subordinate, official and friendly, which have both advantages and disadvantages. The authors also consider models of managerial behaviour, including confrontation, partnership, compromise, avoidance and adaptation. The authors emphasise the need to use an adaptive management style, which involves taking into account the characteristics of the team, motivational mechanisms and social dynamics. It was found that effective leaders have a high level of emotional intelligence, which allows them to respond flexibly to employee requests, maintain positive communication and resolve conflicts. The study also confirmed the importance of a balanced approach to power in an organisation. Excessive control or, conversely, a lack of clear management decisions can have a negative impact on staff motivation and organisational performance. The results obtained may be useful for managers and researchers studying the issues of effective human resource management. Prospects for further research are the development of recommendations for optimising the leadership style, increasing staff motivation and creating an effective communication system in the organisation.